Integrated multichannel Young’s interferometer sensor based on long-range surface plasmon waveguides - Wong, Wei Ru; Berini, Pierre (Optical Society of America, 2019)
Two integrated Young's interferometer (YI) sensors based on long-range surface plasmon polariton (LRSPP) waveguides are presented. The first sensor is single-channel and based on a Y-junction splitter, and the other is multi-channel and based on a corporate feed structure. The multichannel YI enables simultaneous and independent phase-based monitoring of refractive index changes in multiple channels. The diverging output beams from the waveguides are overlapped in the far field to form interference patterns which are then post-processed using the fast Fourier transform (FFT) algorithm to extract phase values. The sensing capability of these YIs was demonstrated through sequential injection of solutions with increasing refractive index into the sensing channels. A detection limit of ∼ 1 × 10−6 RIU was obtained for both LRSPP based YIs, a significant improvement over measurements from similar structures using attenuation-based sensing. © 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement